Effective medium optical modelling of indium tin oxide nanocrystal films. Issue 9 (21st February 2022) - Sygletou, Maria; Marangi, Fabio; Varas, Stefano; Chiasera, Alessandro; Canepa, Maurizio; Scotognella, Francesco; Bisio, Francesco
Abstract : We measure and model the complex dielectric response of indium tin oxide films fabricated by nanocrystal deposition and sintering. Abstract : Doped semiconductor nanocrystal-based thin films are widely used for many applications, such as screens, electrochromic windows, light emitting diodes, and solar cells. Herein, we have employed spectroscopic ellipsometry to measure and model the complex dielectric response of indium tin oxide films fabricated by nanocrystal deposition and sintering. The films could be modelled as Bruggemann effective media, allowing estimation of the nanoscale interstitial porosity of the structure. The effective dielectric constants show the possibility of tuning the plasma frequency and the epsilon-near zero condition of the film.